PENGARUH PERBANDINGAN MASSA ECENG GONDOK DAN TEMPURUNG KELAPA SERTA KADAR PEREKAT TAPIOKA TERHADAP KARAKTERISTIK BRIKET - Iriany; Meliza; Firman Abednego S. Sibarani; Irvan (Talenta Publisher (Universitas Sumatera Utara), 2016)
The purpose of this research is to know the characteristics of briquettes including ash content, moisture content, volatile matter content, heating value, density, burning rate, tensile strength and to know the proper ratio of water hyacinth and coconut shell mixture under tapioca gluten variation. The ratios of water hyacinth and coconut shell in this research were 1:1, 1:2, 1:3, 1:4 with variation of tapioca gluten 5%, 10%, and 15% of the raw materials. From this research, the ideal composition of briquette is obtain in a mixture of water hyacinth and coconut shell at a ratio of 1:4 with tapioca gluten 10%, ash content 9.718%, moisture content 1.374%, volatile matter content 14.814%, heating value 6,879.596 cal/g, density 0.983 g/cm3, burning rate 3.021 × 10-3 g/second and tensile strength 18.400 g/cm2.